1988
DOI: 10.1111/j.1469-8137.1988.tb00285.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenols and bud dormancy

Abstract: SUMMARYQualitative analyses of the endogenous phenols of Fagus sylvatica L. were determined separately in leaf primordia and bud scales of dormant buds (apical, subapical and basal) of Fagus sylvatica L. until bud burst.Qualitative analyses in all leaf primordia showed the presence of phenols which are potential cofactors of I.'\A o.xidase (vanillic acid, 2'4,4'-trihydroxychalcone), uncoupling agents of oxidati\'e phospborylation (norwoponin, orobol 7-O-rhamnoglucoside, baicalin, 2'4,4'-trihydr()xychalcone and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…81 peach buds. Several studies have shown correlation between bud break and seasonal variation of phenols in trees (Codignola et al, 1988b). The evaluation of dormant buds has shown that, phenol compounds rarely occur in a free state within the cell; rather they are commonly conjugated with other molecules.…”
Section: Discussionmentioning
confidence: 99%
“…81 peach buds. Several studies have shown correlation between bud break and seasonal variation of phenols in trees (Codignola et al, 1988b). The evaluation of dormant buds has shown that, phenol compounds rarely occur in a free state within the cell; rather they are commonly conjugated with other molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the maximum amount of phenolic compounds was observed in Jan. at the same time as the deep winter dormancy, which indicates the association of these compounds with cold tolerance and their protective role in dormant buds of the vine. During the dormant phase, a number of growth inhibitors including phenolic compounds (Caffeic acid, Naringin, Phloridzin, Quercitrin) accumulate in the buds of most trees and after getting enough cold in winter, the concentration of these compounds is minimized at bloom (Codignola et al, 1988). It seems that the precipitate of most phenolic compounds in the canes epidermal and buds scales in the cultivars prevents the development of ice crystals within the internal parts of the bud (Chalker-Scott, 1988).…”
Section: Discussionmentioning
confidence: 99%